Transfusion-Transmitted Dengue and Associated Clinical Symptoms During the 2012 Epidemic in Brazil - Sabino, Ester C.; Loureiro, Paula; Lopes, Maria Esther; Capuani, Ligia; McClure, Christopher; Chowdhury, Dhuly; Di-Lorenzo-Oliveira, Claudia; Oliveira, Lea C.; Linnen, Jeffrey M.; Lee, Tzong-Hae; Gonçalez, Thelma; Brambilla, Donald; et al. (The Journal of infectious diseases, 2016)
Background. A linked donor-recipient study was conducted during epidemics in 2 cities in Brazil to investigate transfusion-transmitted (TT) dengue virus (DENV) by DENV RNA–positive donations. Methods. During February–June 2012, samples were collected from donors and recipients and retrospectively tested for DENV RNA by transcription-mediated amplification. Recipient chart review, using a case (DENV positive)–control (DENV negative and not known to be exposed) design, was conducted to assess symptoms. Results. Of 39 134 recruited blood donors, DENV-4 viremia was confirmed in 0.51% of donations from subjects in Rio de Janeiro and 0.80% of subjects in Recife. Overall, 42 DENV RNA–positive units were transfused into 35 recipients. Of these, 16 RNA-positive units transfused into 16 susceptible recipients were identified as informative: 5 cases were considered probable TT cases, 1 possible TT case, and 10 nontransmissions. The TT rate was 37.5% (95% confidence interval [CI], 15.2%–64.6%), significantly higher than the viremia rate of 0.93% (95% CI, .11%–3.34%) in nonexposed recipients (P < .0001). Chart review did not find significant differences between cases and controls in symptoms or mortality. Conclusions. During a large epidemic of DENV-4 infection in Brazil, >0.5% of donations were RNA positive, and approximately one third of components resulted in TT. However, no significant clinical differences were evident between RNA-positive and RNA-negative recipients.